Productivity of grades of oats at different technologies of cultivation - P M Polityko (RUDN Journal of Agronomy and Animal Industries, 2012)
Increase of productivity of summer grain crops at the present stage has great value for an agricultural production. For achievement of an object in view studied reaction of new and perspective grades of an oats at different technologies of cultivation which differ with a level of a mineral feed and to applied means of protection of plants. At observance of technology of cultivation productivity reaches 5-7 ton/hectares.